Ionic Geospatialization and Hydrochemical Characterization of Water Resources around Selected Petroleum Producing Areas in South-Southern Nigeria - Ahmed, Nurudeen Onomhoale; Suleiman, Mohammed Bashir; Olali, Finjite Dorathy; Ogunkoya, Mojisola Mary; Oluwatobi, Fayose Olalekan; Nwuzor, Deborah Ifesinachi Elom (Journal of Applied Geospatial Information, 2024)
Water resources play a crucial role in sustaining life and various socio-economic activities, especially in regions like South-Southern Nigeria, where petroleum production activities are prevalent. This study focuses on understanding the hydrochemical characteristics and geospatial distribution of major ions in water around selected petroleum-producing areas, notably within the Obigbo Local Government Area (L.G.A) of Rivers State. A total of 41 water samples, comprising 34 rain and 7 surface waters, were collected, and analyzed employing hydrochemical modeling techniques, including the Piper Trilinear plot, Durov, and Schoeller diagram, to characterize the ionic composition of surface water and rainwater. The analysis revealed a relatively uniform pattern of major ions, including Ca, Mg, Na, K, HCO3, Cl, SO4, and NO3, across the study area, with higher concentrations observed along the river channel, in the Northern regions. Rainwater samples exhibited lower concentrations, with discernible variations, especially in areas adjacent to petroleum activities. The dominance of Ca + Mg as cations and Cl as anions was consistent in both river water and rainwater samples. Durov diagram depicted a simple dissolution or mixing line in river water, while rainwater samples exhibited a notable presence of calcium and sulphate. The Schoeller diagram indicated a calcium chloride water type, with rainwater showing heightened calcium and sulphate concentrations. Geospatial analysis highlighted consistent ion concentration levels throughout the study area, suggesting environmental stability. Despite concerns about increased sulfate near petroleum facilities, all measured ion concentrations in both river and rainwater samples adhered to WHO standards, indicating satisfactory water quality.